Methodological Principles of the Investigation of People’s Welfare - Dobrovolskas, A. (Problemos, 1978)
The aim of the article is to reveal methodological principles of politico-economic investigation of people’s welfare. The requirements for the investigation of theoretical problems of people’s welfare are disclosed with reference to the classics of Marxism-Leninism. It is shown how the current concepts of people’s welfare correspond to the discovered methodological requirements.